PELATIHAN KETERAMPILAN KERAJINAN TANGAN MENGGUNAKAN MEDIA KERTAS â€œPENGENALAN PAKAIAN DAERAH JAWA BARATâ€ SEBAGAI PROSES KREATIF SISWA PAUD ANGGREK ROSANILA 011 - Widyastuti, Putri Anggraeni; Yusuff, Adisti Ananda (Universitas Esa Unggul, 2020)
With the conditions in the midst of the Covid-19 virus pandemic, it has hampered many teaching institutes that are in the process of teaching and learning. This was experienced by PAUD Anggrek Rosalina 011 in the Tangerang area. Even though they have to carry out learning in accordance with the 2019 PAUD curriculum. Learning is carried out through direct and indirect learning in an integrated and not separate manner through an integrated thematic learning approach designed in the Weekly Learning Implementation Plan and Daily Learning Implementation Plan. To help the solution so that learning continues, the community service design team at Esa Unggul University, consisting of lecturers and students, finally conducted community service activities based on RRPM and RPPM used by PAUD Anggrek Rosalina 011. The activity was in the form of handicraft skills training using paper media